2019
DOI: 10.1128/aem.01620-19
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Fluidity of Saccharomyces cerevisiae from Huangjiu (Chinese Rice Wine) Is Variably Regulated by OLE1 To Offset the Disruptive Effect of Ethanol

Abstract: An evolution and resequencing strategy was used to research the genetic basis of Saccharomyces cerevisiae BR20 (with 18 vol% ethanol tolerance) and the evolved strain F23 (with 25 vol% ethanol tolerance). Whole-genome sequencing and RNA sequencing (RNA-seq) indicated that the enhanced ethanol tolerance under 10 vol% ethanol could be attributed to amino acid metabolism, whereas 18 vol% ethanol tolerance was due to fatty acid metabolism. Ultrastructural analysis indicated that F23 exhibited better membrane integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…The OLE1 gene encoding stearoyl-CoA 9-desaturase catalyzes the transformation of saturated fatty acids (C16:0 and C18:0) to UFAs (C16:1 and C18:1) through a dehydrogenation reaction. Overexpression of OLE1 could improve the fatty acid unsaturation and membrane flexibility, which empower the cells with high tolerance to various types of stress [ 44 46 ]. In the present work, we tested the feasibility of improving cell membrane fluidity by overexpressing OLE1 to enhance β-carotene secretion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The OLE1 gene encoding stearoyl-CoA 9-desaturase catalyzes the transformation of saturated fatty acids (C16:0 and C18:0) to UFAs (C16:1 and C18:1) through a dehydrogenation reaction. Overexpression of OLE1 could improve the fatty acid unsaturation and membrane flexibility, which empower the cells with high tolerance to various types of stress [ 44 46 ]. In the present work, we tested the feasibility of improving cell membrane fluidity by overexpressing OLE1 to enhance β-carotene secretion.…”
Section: Resultsmentioning
confidence: 99%
“…Overproduction of efflux pumps or heterogenous biofuels anchor in the cell membrane can disorganize its structural integrity that impairs vital functions [16]. There are several works demonstrating that improving membrane fluidity by enriching intracellular unsaturated fatty acids (UFAs) can decrease the membrane stress [22,31,44]. Considering that membrane function greatly affects the secretion efficiency of products, we hypothesized that improving the membrane fluidity of host cells may be beneficial to β-carotene secretion.…”
Section: Improving Membrane Fluidity To Enhance β-Carotene Secretionmentioning
confidence: 99%
“…Interestingly, we also found the cell volume of G14 was moderately smaller than the parent. Other researchers have found that the composition change in membrane [ 34 ] or cell wall [ 35 ] is generally associated with the improvement of stress tolerance in industrial strains. Therefore, we inferred that the cell membrane composition and cell wall composition were changed in the G14.…”
Section: Resultsmentioning
confidence: 99%
“…The integrity of cell membranes has also attracted much attention. For example, Yang et al [109] found that S. cerevisiae strain with increasing content of unsaturated fatty acid (UFA) and cell membrane fluidity can tolerate high concentrations (up to 25 vol%) of ethanol. Researchers have found that the increasing content of some amino acids helps yeast to resist environmental stresses.…”
Section: Evident Correlation Among Functional Factorsmentioning
confidence: 99%